2013
DOI: 10.3109/13697137.2013.769097
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low-dose estriol and lactobacilli in the local treatment of postmenopausal vaginal atrophy

Abstract: Objective The aim of this study was to demonstrate the efficacy of an ultra-low-dose vaginal estriol 0.03 mg in combination with viable Lactobacillus acidophilus KS400 (Gynoflor® vaginal tablets) in the short-term therapy and to investigate the long-term maintenance dose in the treatment of vaginal atrophy.Methods This was a double-blind, randomized, placebo-controlled study (Controlled phase – initial therapy) followed by an open-label follow-up (Open phase – test medication initial and maintenance therapy). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 21 publications
0
43
0
1
Order By: Relevance
“…Interestingly, maximum E3 levels were inversely correlated with VMI values, demonstrating that the maturing epithelium rapidly precludes further E3 absorption after initial therapy 53 . Additional flora parameters have also demonstrated positive dynamics in a consistent manner 61,76 . The lactobacillary grade permanently improved from onset through to the end of initial therapy, and even during maintenance therapy 53,61 .…”
Section: Ultra-low-dose Estriol and Lactobacilli Combinationmentioning
confidence: 95%
See 4 more Smart Citations
“…Interestingly, maximum E3 levels were inversely correlated with VMI values, demonstrating that the maturing epithelium rapidly precludes further E3 absorption after initial therapy 53 . Additional flora parameters have also demonstrated positive dynamics in a consistent manner 61,76 . The lactobacillary grade permanently improved from onset through to the end of initial therapy, and even during maintenance therapy 53,61 .…”
Section: Ultra-low-dose Estriol and Lactobacilli Combinationmentioning
confidence: 95%
“…In a pivotal study, Jaisamrarn and colleagues 61 demonstrated the superiority of 0.03 mg-E3/L combination over placebo, with a significantly higher increase in VMI. During initial treatment, VMI increased considerably from the start of treatment to the first follow-up (after 2 weeks of initial therapy) and remained within the normal estrogenization range (> 50%) during 2 months of maintenance therapy 53,61 . Interestingly, maximum E3 levels were inversely correlated with VMI values, demonstrating that the maturing epithelium rapidly precludes further E3 absorption after initial therapy 53 .…”
Section: Ultra-low-dose Estriol and Lactobacilli Combinationmentioning
confidence: 99%
See 3 more Smart Citations